2013
DOI: 10.3390/molecules18078009
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Alkaloids from the Bark of Cryptocarya nigra (Lauraceae)

Abstract: Abstract:A dichloromethane extract of the stem bark of Cryptocarya nigra showed strong in vitro inhibition of Plasmodium falciparum growth, with an IC 50 value of 2.82 μg/mL. The phytochemical study of this extract has led to the isolation and characterization of four known alkaloids: (+)-N-methylisococlaurine (1), atherosperminine (2), 2-hydroxyathersperminine (3), and noratherosperminine (4). Structural elucidation of all alkaloids was accomplished by means of high field 1D-and 2D-NMR, IR, UV and LCMS spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
(36 reference statements)
0
32
0
Order By: Relevance
“…Analysis of the phytochemical constituents of LOE and fractions show that alkaloids, saponins, tannins and flavonoids abundant in the most active fraction, LOMF, may be largely responsible for the antiplasmodial effects of L. owariensis leaf. The antiplasmodial activity of various alkaloids (Saxena et al 2003;Oliveira et al 2009;Nasrullah et al 2013), saponins (Oketch-Rabah et al 1997;Traore et al 2000), tannins (Asres et al 2001) and flavonoids (Saxena et al 2003;Batista et al 2009;Zakaria et al 2012) have been reported. Identification of the antiplasmodial constituent(s) of L. owariensis leaf is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the phytochemical constituents of LOE and fractions show that alkaloids, saponins, tannins and flavonoids abundant in the most active fraction, LOMF, may be largely responsible for the antiplasmodial effects of L. owariensis leaf. The antiplasmodial activity of various alkaloids (Saxena et al 2003;Oliveira et al 2009;Nasrullah et al 2013), saponins (Oketch-Rabah et al 1997;Traore et al 2000), tannins (Asres et al 2001) and flavonoids (Saxena et al 2003;Batista et al 2009;Zakaria et al 2012) have been reported. Identification of the antiplasmodial constituent(s) of L. owariensis leaf is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, the fusion of the two isoquinoline rings (in compound 26) enhances antiplasmodial activity. In another study, Nasrullah et al [34] e N,N-dimethyl groups of the ethylamine side chain (in compounds 33 and 34) are, perhaps, essential for antiplasmodial activity. Malebo et al [35] also isolated four pure alkaloids including palmatine (36) and mixtures of alkaloids from the leaves of Annickia kummeriae.…”
Section: Phenanthroindolizine Alkaloidsmentioning
confidence: 95%
“…Plants of Lauraceae are rich sources of bioactive alkaloids [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. The majority of alkaloids isolated from Beilschmiedia species possess aporphine skeletons ( 71 , Table 3 ) or benzylisoquinoline ( 72 ) skeletons.…”
Section: Chemical Constituentsmentioning
confidence: 99%